In Subtropics... Doubling farmers’ income through technologies - Dutt, Som (Indian Horticulture, 2019)
ICAR-Central Institute for Subtropical Horticulture, Lucknow and Society for Development of Subtropical Horticulture, Lucknow, jointly organized a two-day national conference on ‘Strategies and Challenges in Doubling Farmers’ Income through Horticultural Technologies in Subtropics’ during 21-22 June 2018. There were six technical sessions, viz. Farm Diversification Models in Horticultural Crops for Income Enhancement, Hi-Tech Horticulture for Income Generation, Innovation in Horticultural Crop Management, Value Addition, Entrepreneurship Development and Market Linkages, Breeding and Biotechnology for Better Tomorrow and Emerging Trends in GAP and Management in Horticulture. The sessions were chaired and co-chaired by eminent scientists and academicians. Total 200 participants attended the conference. The technical sessions were deliberated thoroughly and session wise recommendations are furnished here.